Torsional structural behavior of composite rubber hose for offshore applications. (November 2022) - Wei, Daifeng; An, Chen; Wu, Changxu; Duan, Menglan; Estefen, Segen F.
Abstract: Composite offshore rubber hose is a key component for offshore oil transfer. In this work, structural behavior of the offshore rubber hose under torsion is studied. A detailed nonlinear finite element model with rebar technique for offshore rubber hose is established, considering the nonlinear material properties and interactions between components. The effects of different winding angles of cords, the pitches of wire helices and the directions of torsion on hose mechanical performance are studied. The finite element model is validated by the test data and can be a predictive tool for the structural performance of rubber hose under torsion. The results show that the forces in the odd numbered cord layers and the even numbered cord layers are totally different and the pitches of the helix wire and the angles of the cords have a great influence on the torsional stiffness of the rubber hose. Also, when the rubber hose is twisted in the clockwise and anti-clockwise directions, the mechanical properties of inner reinforcement plies and outer reinforcement plies are different and the torsional stiffness displays a nonlinear trend. The effects of some design parameters on the torsional stiffness of the hose are investigated and a prediction formula is obtained. This work can provide theoretical basis and calculation methods for the structural design and integrity evaluation of stiffened composite rubber hose.